SOME KINDS OF SEPARATION AXIOMS ON APPROXIMATION SPACES - hisham jasim (Wasit Journal for Pure Sciences, 2024)
This paper investigates topological features of rough sets and deals with approximation spaces through topological approaches.The traditional separation axioms for topological spaces are extended to approximation spaces. We investigate the connections between the separation axioms for approximation spaces and topological spaces, as well as the approximation spaces they imply.